The impact of medical students' attitudes towards group ethical norms on their academic achievement and classroom deviant behaviour: an empirical study from China - Zang, Zheng (Acta Bioethica, 2022)
In recent years, medical students' absenteeism has been investigated in depth. Classroom deviant behavior is a richer concept thantruancy behavior, but there are few researchers on this aspect in China. There are still many issues worth discussing about deviant classroombehavior. In this paper, questionnaires were given to 977 medical students to collect relevant data. After classifying the data, correlation analysisand multilevel linear regression analysis were used to conclude that academic performance and group ethical norms have a negative impact onmedical students' deviant behaviors in class. Group ethical norms have a significant positive influence on academic performance, and descriptiveethical norms and imperative ethical norms of group ethical norms have a significant influence on academic performance. The four dimensionsof academic performance: academic performance, task performance, interpersonal promotion, and social comparison have a negative influenceon medical students' deviant behaviors in class. Descriptive ethical norms have an inverse effect on medical students' deviant behaviors, whileimperative ethical norms have no significant effect on deviant behaviors in class. Group ethical norms as a category of ethical norms clearly havesignificant implications for improving academic performance and reducing their transgressions in class. Reinforcing group ethics in medicalstudents will not only contribute to their professional ethics upon graduation, but also to their academic performance.